MCR-1 Inhibition with Peptide-Conjugated Phosphorodiamidate Morpholino Oligomers Restores Sensitivity to Polymyxin in Escherichia coli - Seth M. Daly (American Society for Microbiology, 2017)
ABSTRACT In late 2015, the first example of a transferrable polymyxin resistance mechanism in Gram-negative pathogens, MCR-1, was reported. Since that report, MCR-1 has been described to occur in many Gram-negative pathogens, and the mechanism of MCR-1-mediated resistance was rapidly determined: an ethanolamine is attached to lipid A phosphate groups, rendering the membrane more electropositive and repelling positively charged polymyxins. Acquisition of MCR-1 is clinically significant because polymyxins are frequently last-line antibiotics used to treat extensively resistant organisms, so acquisition of this mechanism might lead to pan-resistant strains. Therefore, the ability to inhibit MCR-1 and restore polymyxin sensitivity would be an important scientific advancement. Peptide-conjugated phosphorodiamidate morpholino oligomers (PPMOs) are antisense molecules that were designed to target mRNA, preventing translation. Peptide conjugation enhances cellular entry, but they are positively charged, so we tested our lead antibacterial PPMOs by targeting an essential Escherichia coli gene, acpP, and demonstrated that they were still effective in mcr-1-positive E. coli strains. We then designed and synthesized two PPMOs targeted to mcr-1 mRNA. Five clinical mcr-1-positive E. coli strains were resensitized to polymyxins by MCR-1 inhibition, reducing MICs 2- to 16-fold. Finally, therapeutic dosing of BALB/c mice with MCR-1 PPMO combined with colistin in a sepsis model reduced morbidity and bacterial burden in the spleen at 24 h and offered a survival advantage out to 5 days. This is the first example of a way to modulate colistin resistance with an antisense approach and may be a viable strategy to combat this globally emerging antibiotic resistance threat. IMPORTANCE Polymyxin use has been increasing as a last line of defense against Gram-negative pathogens with high-level resistance mechanisms, such as carbapenemases. The recently described MCR-1 is a plasmid-mediated mechanism of resistance to polymyxins. MCR-1 is currently found in Gram-negative organisms already possessing high-level resistance mechanisms, leaving clinicians few or no antibacterial options for infections caused by these strains. This study utilizes antisense molecules that target mRNA, preventing protein translation. Herein we describe antisense molecules that can be directly antibacterial because they target genes essential to bacterial growth or blockade of MCR-1, restoring polymyxin sensitivity. We also demonstrate that MCR-1 antisense molecules restore the efficacies of polymyxins in mouse models of E. coli septicemia. Considering all things together, we demonstrate that antisense molecules may be effective therapeutics either alone when they target an essential gene or combined with antibiotics when they target specific resistance mechanisms, such as those seen with MCR-1.